Médecins et malades de l'Égypte Romaine : étude socio-légale de la profession médicale et de ses praticiens du Ier au IVe siècle ap. J.-C. - Hirt Raj, Marguerite. (Studies in Ancient Medicine, 2006)
This book is a detailed study of the social and legal position of doctors and their profession in Roman Egypt. It encompasses the formation and the remuneration of doctors, their fields of activities, both professional and lay. It also analyses their socio-cultural milieu and their legal status. In addition, the kinds of medicine practiced, the diseases treated, as well as the therapeutic choices available to the patients are also considered. This study, the first to take into account the whole of the Egyptian material, provides new insights into the daily life of the ordinary practitioners in Egypt, some of which can be extrapolated to those of the Roman world in general.